2020
DOI: 10.3233/bmr-171077
|View full text |Cite
|
Sign up to set email alerts
|

A sonographic comparison of the effect of dry needling and ischemic compression on the active trigger point of the sternocleidomastoid muscle associated with cervicogenic headache: A randomized trial

Abstract: BACKGROUND: Cervicogenic headache (CeH) is among the common types of headache which has an undesirable influence on the quality of life. The myofascial trigger point (MTrP) within the sternocleidomastoid (SCM) muscle is one of the most important causes of CeH. OBJECTIVE: The purpose of this study was to compare the effect of dry needling (DN) and ischemic compression (IC) on the headache symptoms as well as MTrP-related features in subjects with CeH originating from MTrPs of the SCM muscle using a sonographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…A high‐quality RCT 19 compared trigger points dry needling therapy to trigger points manual therapy or to no treatment in adults with CGH. The authors reported significant between group differences in favor of dry needling therapy compared to no treatment for headache frequency (MD: −1.45 episodes/week; 95% CI: −4.53 to −1.26; n = 20), headache intensity (MD VAS 0‐10: −3.14 points/10; 95% CI: −3.96 to −2.30; n = 20), and headache duration (MD: −6.46 h/day; 95% CI: −8.41 to −4.52; n = 20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high‐quality RCT 19 compared trigger points dry needling therapy to trigger points manual therapy or to no treatment in adults with CGH. The authors reported significant between group differences in favor of dry needling therapy compared to no treatment for headache frequency (MD: −1.45 episodes/week; 95% CI: −4.53 to −1.26; n = 20), headache intensity (MD VAS 0‐10: −3.14 points/10; 95% CI: −3.96 to −2.30; n = 20), and headache duration (MD: −6.46 h/day; 95% CI: −8.41 to −4.52; n = 20).…”
Section: Resultsmentioning
confidence: 99%
“…If not, appraisal was conducted independently by two authors (A.D. and C.G.) 13,19‐21 . The final score was obtained through consensus.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it appears that the same mechanism, i.e., increased tissue temperature, was responsible for the positive treatment effect on ankle ROM observed here as well. As latent TrP causes muscle dysfunction [6,39], the thermal effect of the US-KHz might also explain the demonstrated improvement in the Side Hop Test [6]. Previous studies have shown positive effects of US-MHz frequencies on latent and active TrP in terms of ROM, PPT, pain relief, disability, and quality of life [11,[40][41][42][43][44], however, no studies have as yet compared the effects of low frequency (KHz) and high frequency (MHz) US on TrPs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, while latent TrPs are not associated with spontaneous discomfort, local and referred symptoms may be provoked by mechanical stimulation, such as finger pressure exerted over the latent TrPs [4]. Similar to active TrPs, latent TrPs may restrict the range of motion (ROM) and may lead to muscle dysfunction, i.e., muscle weakness, muscle imbalance, or altered motor unit recruitment patterns [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…12 There were multiple clinical studies reporting that pressing on MTrPs could alleviate muscular pain, contributing to increased function and range of movement. [13][14][15] Moreover, pressing could be applied in combination with other therapies to bring more favorable efficacy, for example, alleviate the sore feeling resulted from acupuncture on MTrPs. 16,17 Despite the definite clinical efficacy of pressing treatment, its mechanism has not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%